Regional capital market - Bissember, Enid ([Caribbean Center for Money & Finance] [St. Augustine]TT, 1995)
Looks at the development of the capital market in the CARICOM Region and highlights the initiatives which are being taken to create a regional capital market. Focuses on the benefits to be derived, the factors affecting cross border flows and the impediments to the growth of the market.